LncRNA BLACAT1 is involved in chemoresistance of non‑small cell lung cancer cells by regulating autophagy - Fengxiang Huang; Hongjie Chen; Fu‐Xia Zheng; Zeng‐Yan Gao; Pan‐Feng Sun; Qiang Peng; Ying Liu; Xiang Deng; Ya‐Hui Huang; Chang Zhao; Lijun Miao (2018)
The aim of the present study was to determine the effect of the long non‑coding RNA (lncRNA) bladder cancer‑associated transcript 1 (BLACAT1) in chemoresistance of non‑small cell lung cancer (NSCLC) cells. Expression of lncRNA BLACAT1, microRNA (miR)‑17, autophagy‑related protein 7 (ATG7), multidrug‑resistance protein 1 (MRP1), and the autophagy‑associated proteins light chain 3 (LC3)‑II/LC3‑I and Beclin 1 were detected using the reverse transcription‑quantitative polymerase chain reaction and western blot analysis. Cell viability was determined using an MTT assay. The interaction between BLACAT1 and miR‑17 was determined using RNA immunoprecipitation and RNA pull‑down assays. A cisplatin (DDP)‑resistant NSCLC cell A549/DDP xenograft model in nude mice was established to investigate the effect of BLACAT1 on the chemoresistance of NSCLC cells. Compared with in DDP‑sensitive NSCLC cells, expression of BLACAT1, ATG7, MRP1, LC3‑II/LC3‑I and Beclin 1 was significantly upregulated in DDP‑resistant NSCLC cells, whereas miR‑17 was downregulated in DDP‑resistant NSCLC cells. Short interfering RNA against BLACAT1 decreased the viability of DDP‑resistant NSCLC cells. In addition, BLACAT1 interacted with miR‑17, and negatively regulated miR‑17. BLACAT1 promoted ATG7 expression through miR‑17, and facilitated autophagy and promoted chemoresistance of NSCLC cells through miR‑17/ATG7. Finally, in vivo experiments indicated that inhibition of BLACAT1 ameliorated the chemoresistance of NSCLC. BLACAT1 was upregulated in DDP‑resistant NSCLC cells, and promoted autophagy and chemoresistance of NSCLC cells through the miR‑17/ATG7 signaling pathway.